Pomen družinskih oskrbovalnih dejavnosti v življenju mladih ljudi, živečih v Ljubljani ali okolici - Hlebec, Valentina (Družboslovne razprave, 2019)
Young family carers are people who in their everyday lives provide care to members of their family. This means they do things, often on a regular basis, which are usually associated with adults. In Slovenia, young carers are an invisible population and a neglected research topic. The data from Youth in Ljubljana 2017 give us the first insights into the characteristics of young carers in Slovenia. The dependent variable in our regression analysis is the subjective meanings young people attribute to caring activities within the family. Family caring activities are more important to young women, households with siblings, and religious children. Greater importance is associated with both increasing age and permanent residence in Ljubljana. Moreover, the higher importance of family caring activities is associated with lower school success.
Keywords: Družina; družinska oskrba; Family; Mladina; neformalna oskrba; Youth